2023
DOI: 10.3390/agriculture13040850
|View full text |Cite
|
Sign up to set email alerts
|

QTL×QTL×QTL Interaction Effects for Total Phenolic Content of Wheat Mapping Population of CSDH Lines under Drought Stress by Weighted Multiple Linear Regression

Abstract: This paper proposes the use of weighted multiple linear regression to estimate the triple3interaction (additive×additive×additive) of quantitative trait loci (QTLs) effects. The use of unweighted regression yielded an improvement (in absolute value) in the QTL×QTL×QTL interaction effects compared to assessment based on phenotypes alone in three cases (severe drought in 2010, control in 2012 and severe drought in 2012). In contrast, weighted regression yielded an improvement (in absolute value) in the evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…Ahmad et al [19] also reported that the correlation coefficient and direct effect of biological yield on grain yield are the highest. It was reported that the effect of biological yield on grain yield is significant even in drought-stressed wheat [31,46]. In addition, the results of the study are consistent with studies on durum wheat [47] and bread wheat [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…Ahmad et al [19] also reported that the correlation coefficient and direct effect of biological yield on grain yield are the highest. It was reported that the effect of biological yield on grain yield is significant even in drought-stressed wheat [31,46]. In addition, the results of the study are consistent with studies on durum wheat [47] and bread wheat [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…However, the use of weighted regression shows that the difference between the phenotypic and genotypic estimation can be reduced, and the total genetic effects will be closer to the true value. Similar results were obtained by estimating QTL-QTL-QTL triple interaction effects for total phenolic content in the mapping population of wheat doubled haploid lines under drought stress conditions [30].…”
Section: Data Setsupporting
confidence: 78%
“…The above results concern QTL–QTL–QTL interaction effects obtained by the simplest possible methods, i.e., using multiple linear regression on the marker data. Cyplik et al [ 30 ] showed that modifying this regression by using empirical weights provides a better agreement between phenotypic and genotypic estimates.…”
Section: Introductionmentioning
confidence: 99%
“…On both dates (the first and fourteenth day of drought), the genotype had a significant impact on the content of phenolic compounds, which indicates a different reaction of the tested OMA lines to water deficiency. In experiments on drought stress in spring triticale, an increase in the content of phenolic compounds was found, and this parameter was considered useful in selecting genotypes less susceptible to drought stress [ 46 ]. In potatoes, increased content of phenolic compounds was also observed as a result of drought, during which the analyzed secondary metabolites were responsible for the good general condition of plants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%